Towards economic processing of high performance garnets – case study on zero Li excess Ga-substituted LLZO. Issue 11 (17th February 2023) - Schwab, Christian; Häuschen, Grit; Mann, Markus; Roitzheim, Christoph; Guillon, Olivier; Fattakhova-Rohlfing, Dina; Finsterbusch, Martin
Abstract : In this processing study we systematically investigate the impact of lithium excess and dwell time on Ga-substituted LLZO:Ga and show that Li-excess during synthesis and processing is a critical parameter to obtain peak performance. Abstract : In this processing study we systematically investigate the impact of lithium excess and dwell time on Ga-substituted LLZO (Li6.4 Ga0.2 La3 Zr2 O12 ). To draw a holistic picture of the underlying dependencies for maximum performance, we study the composition, phase formation, density and microstructure, especially with respect to the grain boundaries, in detail. For the first time, we show that Li-excess during synthesis and processing is not just unnecessary for LLZO:Ga, but that high amounts of Li excess can also prevent obtaining peak performance or increase energy and precursor consumption to a non-feasible level for industrial application. We show that the underlying mechanism is an intricate interplay between phase equilibria of different phases (tetragonal, cubic, Li–La–Ga), which have good conductivity and/or act as sintering aids (in low amounts) but are detrimental to electrochemical performance in large amounts. Based on this understanding, we developed a reproducible and robust processing route for LLZO:Ga, minimizing Li excess and dwell time while maintaining high conductivity in the final component. This can make the LLZO family more viable for application in high energy density all-solid-state batteries and provide a pathway for economic industrial processing.